A Survey on Algorithms for Limited Resources Optimization and Utilization by Games on Smartphones - Natumanya, Deorah; Nabaasa, Evarist; Mugonza, Robert (International Journal of Computer Applications, 2016)
Smartphones have been characterized by their limited computational resources such as battery life, processor performance and storage capacity. The above mentioned limitations can be overcome by utilizing mobile cloud computing where the smartphone can utilize the sufficient cloud resources. A number of solutions have been suggested and developed to alleviate the issues with smartphone resource limitations however they are not efficient. This paper provides an overview on the existing algorithms for accessing resource hungry applications on the cloud clearly indicating their techniques and flaws. The paper also describes the directions for the future research.
Keywords: Mobile Cloud Computing; Algorithms; Smartphones; Resource Hungry Games